New insight into the levels, distribution and health risk diagnosis of indoor and outdoor dust-bound FRs in colder, rural and industrial zones of Pakistan. (September 2016) - Khan, Muhammad Usman; Li, Jun; Zhang, Gan; Malik, Riffat Naseem
Abstract: This is the first robust study designed to probe selected flame retardants (FRs) in the indoor and outdoor dust of industrial, rural and background zones of Pakistan with special emphasis upon their occurrence, distribution and associated health risk. For this purpose, we analyzed FRs such as polybrominated diphenylethers (PBDEs), dechlorane plus (DP), novel brominated flame retardants (NBFRs) and organophosphate flame retardants (OPFRs) in the total of 82 dust samples (indoor and outdoor) collected three from each zone: industrial, rural and background. We found higher concentrations of FRs (PBDEs, DP, NBFRs and OPFRs) in industrial zones as compared to the rural and background zones. Our results reveal that the concentrations of studied FRs are relatively higher in the indoor dust samples being compared with the outdoor dust and they are ranked as:∑ OPFRs > ∑ NBFRs > ∑ PBDEs > ∑ DP. A significant correlation in the FRs levels between the indoor and outdoor dust suggest the potential intermixing of these compounds between them. The principal component analysis/multiple linear regression predicts the percent contribution of FRs from different consumer products in the indoor and outdoor dust of industrial, rural and background zones to trace their source origin. The FRs detected in the background zones reveal the dust-bound FRs suspended in the air might be shifted from different warmer zones or consumers products available/used in the same zones. Hazard quotient (HQ) for FRs via indoor and outdoor dust intake at mean and high dust scenarios to the exposed populations (adults and toddlers) are found free of risk (HQ < 1) in the target zones. Furthermore, our nascent results will provide a baseline record of FRs (PBDEs, DP, NBFRs and OPFRs) concentrations in the indoor and outdoor dust of Pakistan. Graphical abstract: Highlights: The first report on PBDEs, DP, NBFRs & OPFRs concentration in indoor & outdoor dust. The first time detection of FRs in background zones of Pakistan have been investigated. Significant correlation in FRs levels between indoor & outdoor dust were observed. HQ for targeted FRs to toddlers and adults via indoor & outdoor dust intake was <1. Abstract : The first report indicates different levels of dust bound FRs between indoor and outdoor environments as well as sources and risk diagnosis at different altitudinal zones of Pakistan.